Minha alma canta, vejo o Rio de Janeiro': a zona sul carioca entre crônicas e canções - Santos, Vicente Saul Moreira dos (2013)
This thesis addresses the pro cess of valuing the South Zone of Rio de Janeiro through songs that focused on this space, besides chronicles, especially, published in the book O Rio de Janeiro em Prosa e Verso , organized by Manuel Bandeira and Carlos Drummond de Andrade . To organize this complex relationship between music and the city, between literary production and the city, this paper is organized into five ch apters. In the first chapter, I focused the fourth centenary celebrations of the City of Rio de Janeiro held in 1965, the carnival this year dedicated to the anniversary and some public ations motivated by the event. In the second, I wrote about the occupation of the urban space called South Zone of Rio, especially through the chronicles in the book listed above. The next chapte r highlighted the importance of nightclubs, bars, casinos and other cultural spaces of sociability in the South Zone of Rio, as places of education and artistic experience, where they were hatc hed important solidarity networks and friendship. In the fourth chapter we have presented some songs that priori tized Rio, the representations in lyrics and music of South Zone, especially Copacabana, as one of the most prioritized neighborhoods of Rio seen in this collection. Finally, Bossa Nova was shown as indelible moment to debate the identity of the Carioca city, its international projecti on and how Rio was presented by its lyrics.